Quality of life of women undergoing treatment for cervical cancer - Francieli Ana Dallabrida; Marli Maria Loro; Cleci de Lourdes Schmidt Piovesan Rosanelli; Marina Mazzuco de Souza; Joseila Sonego Gomes; Adriane Cristina Bernat Kolankiewicz (Universidade Federal do Ceará, 2014)
This study aimed to evaluate the quality of life of women with cervical cancer. This is a cross-sectional, descriptive study developed with 43 women undergoing oncological treatment assisted at an Oncology High Complexity Center, in the Southern region of Brazil. The instrument used was the European Organization for Research and Treatment of Cancer - Quality of Life Questionnaire Core-30, and the data were analyzed through descriptive statistics. The average age was 54.6 years old. Married women prevailed (53.4%), with incomplete elementary education (72.1%) and income from one to two minimum wages (62.8%). Quality of Life was considered very satisfactory. According to the development scales and emotional functioning, the result was from regular to satisfactory. The most frequent symptoms were fatigue, lack of appetite and pain. There is a need of structure of public health policies, for preventing cervical cancer in the most vulnerable population.